Aprendizagem de Língua Inglesa mediada por sítios: uma atividade promovida em um centro de autoacesso - BORGES, Kleiton de Sousa (Universidade Federal do Pará, 2019)
The Applied Linguistics (AL) studies in the area of teaching and learning languages have been conducted in an interdisciplinary way. One of the themes of these studies is the research on autonomy in language learning in order to understand how this process is instigated in learners from diverse learning situations. New technologies, as Computer Assisted Language Learning (CALL) and Information and Communication Technologies (ICT) are tools that can stimulate the development of this autonomy. These tools are present in educational institutions and in the daily life of teachers and students, enabling learning of a foreign language (FL) in an effective way (LEFFA, 2006; OLIVEIRA, 2012; ANDRADE, 2014; ARAÚJO, 2017). ICT is also used in self-access centers (SAC) in order to foster the autonomous studies of language learners in these spaces (GARDNER; MILLER, 1999; BARRS, 2010; MAGNO E SILVA, 2014; MYNARD, 2016). This work aimed to understand in what ways the activities mediated by computers, through sites, could influence the English language learning of students who attend and participate in activities at Base de Apoio à Aprendizagem Autônoma (BA3), a self-access center located at the Faculdade de Letras Estrangeiras Modernas (FALEM) of the Federal University of Pará (UFPA). A case study was conducted employing a quanti-qualitative approach with observation and application of on-line questionnaires. The results showed that English language learning sites influenced positively the development of participants' autonomy, since they began to use these sites on their own to practice by listening, reading and speaking English. It was also found that the good layout and the types of activities of these sites were important items which led learners to use them.